Patogenicidade e virulência de Beauveria bassiana e Metarhizium anisopliae a Euschistus heros (Hemiptera: Pentatomidae) - Oliveira, Darlin Henrique Ramos de (2017)
Soybean yield, Glycine max (L.) Merrill (Fabaceae), plays a strategic role in economic and social development towards agriculture, especially as a resource of protein for human and animal diet. Euschistus heros (Fabricius, 1798) (Hemiptera: Pentatomidae), commonly known as neotropical brown stink bug is a major pest of soybean due to damage to pods and grains, reducing yields and consequently the quality (vigor and germination) of the seeds. With the rise of production and consumption of organic foods, especially organic soy, requires alternatives methods of control that can be efficient and at the same time not harmful to the environment. Biological control with entomopathogenic fungi might be a profitable strategy due to the broad spectrum of action of the pathogen. Entomopathogenic fungi products are used to control several species of insect pests, including hemiptera, however, the effects of these fungi on E. heros are limited. The aim of this work was to evaluate the pathogenicity and virulence of different concentrations of commercial products based on Metarhizium anisopliae and Beauveria bassiana on E. heros under laboratory conditions. For this, the products were obtained from an agricultural supply store and prepared suspensions at the dosages of 500 g ha1, 1000 g ha-1, 2000 g ha-1 e 4000 g ha-1, at concentrations of 1,0x108 and 1,39x108 conidia g-1, respectively for B. bassiana and M. anisopliae. The products in the different dosages were applied in 1) 24 hour eggs, 2) third instar nymphs and 3) E. heros adults. Each treatment (dosage) had four replicates of 20 eggs each (1) and / or 15 insects (2 and 3). The fungi were applied by immersion in 1 mL for (1) and 2 mL of the suspensions for (2 and 3), in a 50 mL volumetric vessel. The control samples were treated without application and with distilled water + Tween 80® (0.01%). The plates were conditioned in a climatic chamber at a temperature of 27 ± 2oC, relative humidity of 70 ± 10% and photophase of 12 hours. The evaluation was performed daily for 10 days, quantifying daily hatching (1) and daily mortality (2 and 3). There was no ovicidal effect of the bioinsecticides on E. heros under laboratory conditions. The treatments consisting of fungi B. bassiana and M. anisopliae presented pathogenicity and virulence on E. heros nymphs, with B. bassiana being the bioinseticide at the dosage of 4000 g ha-1 (95%) the treatment that presented the greater virulence. For E. heros adults, all treatments using the entomopathogenic fungi (B. bassiana and M. anisopliae) bioinsecticides showed pathogenicity and virulence effects under laboratory conditions. The other treatments did not present significant results. Aiming at the need to develop new alternatives for pest control in agroecological systems of production, other studies and the development of future fieldwork are necessary.